MODELING OF ALKYL SALICYLATE COMPOUNDS AS UV ABSORBER BASED ON ELECTRONIC TRANSITION BY USING SEMIEMPIRICAL QUANTUM MECHANICS ZINDO/s CALCULATION - Iqmal Tahir; Karna Wijaya; Titik Subarni (Universitas Gadjah Mada, 2002)
Modeling of several alkyl salicylates based on electronic transition by using semiempriical mechanical quantum ZINDO/s calculation has been done. Object of these research were assumed only alkyl salicylates of C4 (butyl) until C8 (octyl) homologue with 4-7 example structures of each homologue. All of the computation have been performed using quantum chemistry - package software Hyperchem 6.0. The research covered about drawing each of the structure, geometry optimization using semiempirical AM1 algorithm and followed with single point calculation using semiempirical ZINDO/s technique. ZINDO/s calculations used a defined criteria that is singly excited - Configuration Interaction (CI), gap of HOMO-LUMO energy transition was 2 and degeneracy level was 3. Analysis of the theoretical spectra was focused in the UV-B (290-320 nm) and UV-C (200-290 nm) area. The result showed that modeling of the compound can be used for predicting the type of UV protection activity depending with the electronic transition in the UV area. Modification of the alkyl homologue relatively did not change the value of wavelength absorbtion to indicate the UV protection activity. Alkyl salicylate compounds were predicted as UV-C sunscreen or relatively the compounds have protection effect for UV-C.